Fuzzy sliding mode control of a structure based on hedge algebras containing input time delay - Le, Bui Hai; Anh, Le Tung; Binh, Bui Van; Hoan, Nguyen Thai Tat (Vietnam Journal of Science and Technology, 2019)
In this paper, the authors present the sliding mode control problem of a structure using hedge-algebras-based fuzzy controller considering the impact of time delay (de-sHAC). Controlled model is a structure subjected to earthquake excitations. Numerical simulations are implemented in order to show advantages of the proposed controller. Obtained results include: variation of maximum displacement and maximum absolute acceleration versus time delay; time responses of displacement, absolute acceleration and control force of the structure in the uncontrolled case, the controlled case using the hedge-algebras-based fuzzy controller with input time delay (de-HAC) and the de-sHAC.